PENERAPAN MODEL PEMBELAJARAN AIR (AUDITORY, INTELLECTUALLU, REPETITION) TERHADAP HASIL BELAJAR - Rosa, Farah Maulidya; Tatik Indayati (Sindoro: Cendikia Pendidikan, 2024)
Law Number 20 of 2003 concerning National Education states that education is a conscious and structured effort to create a learning environment and continuity of learning, enabling students to be active in developing their potential, so that they have skills in the fields of religion, self-control, character, skills, morals. good things that society will need. This study aims to determine the improvement of students' learning outcomes through the application of AIR (Auditory, Intellectually, Repetition) learning model and evaluate the implementation of the model. The methodology used involved an experimental class that applied the AIR model and a control class that used the conventional learning model. Data were collected through learning outcome tests, and analyzed using prerequisite test, T test, and gain value. The analysis results showed that all pretest and posttest data from both groups were normally distributed, allowing the application of parametric statistical analysis. The t-test revealed significant differences between the learning outcomes of the experimental and control classes, with the experimental class achieving a higher mean. Although most respondents had N-gains in the Moderate category, there were variations in performance improvement, with some respondents showing high N-gains. Overall, the application of the AIR (Auditory, Intellectually, Repetition) learning model was proven effective in improving students' understanding and skills, thus concluding that this model is more effective compared to conventional learning methods. penelitian ini dilatar belakangi hasil belajar siswa rendah karena menggunakan model pembelajaran konvensional. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa melalui penerapan model pembelajaran AIR (Auditory, Intellectually, Repetition). Metodologi penelitian menggunakan menggunakan quasi eksperimental dengan tipe Non-equivalen Control Group Design. Penentuan sampel menggunakan teknik purposive sampling. Data dikumpulkan melalui tes hasil belajar dan lembar observasi. Untuk tes yaitu menggunakan tes hasil belajar dan lembar observasi untuk melihat keterlaksanaan model pembelajaran AIR. Analisis data menggunakan uji validitas expert judgment , uji prasyarat, uji t, nilai gain, dan presentase analisis keterlaksanaan model pembelajaran AIR. Hasil menunjukkan bahwa semua data pretest dan posttest dari kedua kelompok berdistribusi normal, sehingga memungkinkan untuk menggunakan analisis statistik parametrik. Uji-t menunjukkan sig (2 tailed) 0,000 pada kelas eksperimen dengan nilai <0,005 menyatakan ada perbedaan peningkatan hasil belajar siswa menggunakan model pembelejaran AIR dan model pembelajaran konvensional. Dari n-gain dalam kelas eksperimen memiliki kategori sedang dengan nilai 0,535 sehingga ada peningkatan hasil belajar dengan menggunakan model pembelajaran AIR. Keterlaksanaan model pembelajaran AIR adalah 93,3% dengan kategori sangat efektif pada aktivitas guru, sedangkan pada aktivas siswa adalah 89% dengan kategori sangat efektif.